2018
DOI: 10.1038/s41598-018-26311-w
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic insights into the microbial diversity in manganese-contaminated mine tailings and their role in biogeochemical cycling of manganese

Abstract: To extend the knowledge on the microbial diversity of manganese rich environments, we performed a clone library based study using metagenomic approach. Pyrosequencing based analysis of 16S rRNA genes were carried out on an Illumina platform to gain insights into the bacterial community inhabiting in a manganese mining site and the taxonomic profiles were correlated with the inherent capacities of these strains to solubilise manganese. The application of shot gun sequencing in this study yielded results which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(20 citation statements)
references
References 46 publications
5
12
0
Order By: Relevance
“…In general, Proteobacteria prevailed in the soil with the highest concentrations of metal(loid)s (soil C), whereas Actinobacteria dominated in the soil with the lowest concentrations (A). These results are in tune with several studies that reported a high abundance of Proteobacteria and a low abundance of Actinobacteria in soils with elevated concentrations of metals and As (Epelde et al, 2015;Feng et al, 2018;Ghosh & Das, 2018;Luo et al, 2014). The greater abundance of Proteobacteria in the most contaminated soil could be related to the fact that they are Gram-negative bacteria, whose characteristic feature is the presence of an outer lipopolysaccharide (LPS) layer in their cell wall.…”
Section: Structure Of the Microbial Communitysupporting
confidence: 87%
See 1 more Smart Citation
“…In general, Proteobacteria prevailed in the soil with the highest concentrations of metal(loid)s (soil C), whereas Actinobacteria dominated in the soil with the lowest concentrations (A). These results are in tune with several studies that reported a high abundance of Proteobacteria and a low abundance of Actinobacteria in soils with elevated concentrations of metals and As (Epelde et al, 2015;Feng et al, 2018;Ghosh & Das, 2018;Luo et al, 2014). The greater abundance of Proteobacteria in the most contaminated soil could be related to the fact that they are Gram-negative bacteria, whose characteristic feature is the presence of an outer lipopolysaccharide (LPS) layer in their cell wall.…”
Section: Structure Of the Microbial Communitysupporting
confidence: 87%
“…Most studies on the microbial communities of contaminated mine soils have focused primarily on taxonomic analysis and diversity, pointing out differences in abundance among large groups such as phyla and classes (Hemmat-Jou et al, 2018;Rastogi et al, 2010;Xiao et al, 2019). These works have been carried out mainly by amplicon sequencing, the resolution of which does not allow one to classify with sufficient accuracy the microorganisms at the genus and species level, studies on mine soil microorganisms carried out with whole-metagenome shotgun sequencing still being scarce due to the high cost (Ghosh & Das, 2018;Luo, Bai, Liang, & Qu, 2014). In order to identify particular species that are tolerant of metal contamination and have the potential to be used as biofertilizers with phytoremediation plants in mining sites, studies based on these whole-metagenome shotgun sequencing techniques are required, including comprehensive taxonomic and functional analyses even at low taxonomic ranks.…”
Section: Introductionmentioning
confidence: 99%
“…Last decade, several studies have been documented by using a metagenomics approach to explore the microbial diversity, community structure or composition, and seasonal variation in marine environments ( Gilbert et al, 2009 , Gilbert and Dupont, 2011 , Gilbert et al, 2012 , Won et al, 2017 ). Moreover, metagenomic approaches of the microbial communities in manganese mining revealed their role in the natural manganese geochemical cycle ( Gosh and Das, 2018 ). The microbial diversity play an important role in oceanic productivity, major biomass and nutrient recycling in the coastal and marine environment ( Nair et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfate is highly concetrated in the borehole fluids and is likely a major component in sulfur reducing metabolisms [37,38]. The positive correlation between Mn and Zn (Figure 2) demonstrates a relationship between the metals concentrations and the borehole fluid origin ;which can be indicative of the host environment for microbial communities [39][40][41]. Boreholes 2 and 3 contain the greatest amounts of the metals, while Boreholes 6 and 8 contain the lowest concentrations.…”
Section: Geochemical Dynamicsmentioning
confidence: 97%